Revisions of potential output estimates in the EU after the Great Recession - Dovern, Jonas; Zuber, Christopher (CESifo working papers, 2019)
Using European Commission real-time data, we show that potential output (PO) estimates were substantially and persistently revised downwards after the Great Recession. We decompose PO revisions into revisions of the capital stock, trend labor, and trend total-factor productivity (TFP). Initially, trend TFP revisions contribute most to the overall PO revisions while all three components are almost equally important in the longer run. Revisions of the capital stock happen quickly while revisions of trend labor, mainly driven by revisions of the non-accelerating wage rate of unemployment (NAWRU), are made gradually. The relative contributions of the components to overall PO revisions differ systematically across countries. This suggests that heterogeneous policies are needed to push different countries back to their previous growth paths.
Keywords: Graue Literatur